2007
DOI: 10.1016/j.jaci.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Cockroach allergen reduction by cockroach control alone in low-income urban homes: A randomized control trial

Abstract: Background-We previously reported significant reductions in cockroach allergen concentrations in urban homes by reducing cockroach infestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 17 publications
3
52
0
4
Order By: Relevance
“…Cockroach allergen is one of the strongest risk factors for asthma among inner city residents [38]. Studies suggest that exposure to high levels of cockroach allergen in sensitized asthmatic individuals is associated with increased symptoms and risk of exacerbation [39].…”
Section: Cockroachmentioning
confidence: 99%
See 1 more Smart Citation
“…Cockroach allergen is one of the strongest risk factors for asthma among inner city residents [38]. Studies suggest that exposure to high levels of cockroach allergen in sensitized asthmatic individuals is associated with increased symptoms and risk of exacerbation [39].…”
Section: Cockroachmentioning
confidence: 99%
“…A 2007 randomized controlled study by Sever and colleagues [38] compared the effects of two different abatement measures on cockroach populations and allergen levels within infested homes. The houses were randomly assigned to receive treatment by commercial pesticide companies, treatment by strategically positioned bait traps placed by entomologists, or to a nontreatment control group.…”
Section: Exposure Mitigationmentioning
confidence: 99%
“…Until recently, however, there has been sparse evidence that cockroach control alone could attain longterm, clinically relevant reductions in cockroach allergens in infested structures. Sarpong et al (1996) and Sever et al (2007) clearly showed that cockroach control alone signiÞcantly reduced cockroach allergen levels in homes. The effect of cockroach control has not been shown in school settings, even though many schoolsÑin both urban and rural districtsÑare prone to cockroach infestations and have clinically relevant cockroach allergen levels (Sarpong et al 1997, Abramson et al 2006, Perry et al 2008).…”
mentioning
confidence: 97%
“…Both active methods reduced infestation and cockroach allergen levels, but the magnitude of reduction was dependent on the thoroughness of the eradication effort. 15 …”
Section: Allergy Exposure Assessment and Reductionmentioning
confidence: 99%